2022
DOI: 10.1063/5.0125989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anisotropy on the stability of Giesekus fluid flow

Abstract: In the present work, the stability of a viscoelastic fluid flow is studied by Linear Stability Theory (LST), and some results are verified by Direct Numerical Simulation (DNS). The investigation considers the fluid flow between two parallel plates, modelled by the Giesekus constitutive equation. The results show the influence of the anisotropic tensorial correction parameter $\alpha_G$ on this model, showing a stabilizing influence for two-dimensional disturbances for small values of $\alpha_G$. However, as $\… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Joens et al 11 developed a comprehensive framework for analyzing the time-dependent motion of an isolated, torque-free sphere in a weakly viscoelastic fluid, as exemplified by the Giesekus model, in a trajectory that is not restricted to translation in a single direction. Furlan et al 12 investigated how the mobility parameter of the Giesekus model affects the stability of planar Poiseuille flow. Through a linear stability analysis, they found that smaller values of the mobility parameter stabilize two-dimensional perturbations but increase instability in three-dimensional ones.…”
mentioning
confidence: 99%
“…Joens et al 11 developed a comprehensive framework for analyzing the time-dependent motion of an isolated, torque-free sphere in a weakly viscoelastic fluid, as exemplified by the Giesekus model, in a trajectory that is not restricted to translation in a single direction. Furlan et al 12 investigated how the mobility parameter of the Giesekus model affects the stability of planar Poiseuille flow. Through a linear stability analysis, they found that smaller values of the mobility parameter stabilize two-dimensional perturbations but increase instability in three-dimensional ones.…”
mentioning
confidence: 99%